Comparative Analysis of Direct and Indirect 131I Measurement Methods from the Stack to Outdoor - G. Suhariyono; B Bunawas (PPIKSN-BATAN, 2017)
The radioisotope production facility at PUSPIPTEK Serpong produces and processes 131I that can disperse to the settlements (community) and the environment around the Serpong Nuclear Area (SNA). 131I is produced routinely for medical uses in hospitals and pharmacies, for both domestic uses and export. 131I is a beta and gamma emitting radioactive material and can cause thyroid cancer. The problem was that there was so far no research and in-depth assessment of the aerial dispersion of 131I radioactivity emitted from the radioisotope production stack to the environment at actual conditions. The research was conducted through simultaneous measurement of 131I radioactivity in the stack of the 131I radioisotope production facility, Serpong, and outdoor in house courtyards around SNA in normal condition (no accident) based on the variations of the distance and wind direction. Direct measurements were carried out with a portable in-situ NaI(Tl) detector at outdoor, and with a LaBr3 detector in the stack. Indirect measurements were carried out by using charcoal filter and vacuum pump in the stack and outdoor. The direct measurement method has many advantages over the indirect measurement. The direct measurement method was found to be more accurate, less expensive, easier to operate, needing just one operator in its implementation, portable, and can be operated continuously and for long durations. The overall activity concentrations of 131I on average obtained by either direct or indirect method were still below the upper limit of 131I activity concentration in the air (530 Bq/m3) stipulated by the Regulation of the Chairman of BAPETEN (Perka BAPETEN) No. 7/2013.